Stabilization of γ-sterilized low-density polyethylene by synergistic mixtures of food-contact approval stabilizers - Alariqi, Sameh A. S.; Al-Areqi, Niyazi A. S.; Alaghbari, Elyas Sadeq; Singh, Raj Pal (International Journal of Industrial Chemistry, 2017)
In our previous studies, we have found the synergistic combinations of stabilizers which follow different mechanisms of stabilization and are approved for food contact applications. The present attempt is to test the potentials of those systems in stabilizing γ-sterilized low-density polyethylene (LDPE). The results were discussed by comparing the stabilizing efficiency of mixtures with and without phenol systems as well as with their counterparts of isotactic polypropylene (iPP) and ethylene-propylene copolymers (EP) matrices. LDPE has been melt-mixed with tertiary hindered amine stabilizer (tert-HAS), oligomeric HAS stabilizer, phenolic and organo-phosphite antioxidants and subjected to γ-sterilization. Stabilization in terms of changes in oxidation products, tensile properties, yellowing and surface morphology was evaluated by FT-IR spectroscopy, Instron, colorimetry, and scanning electron microscopy (SEM), respectively. The results of the present study confirm the validity of those systems for protecting various polyolefins against γ-sterilization. The results showed that the synergism, antagonism and the trend in stabilization efficiency of the binary, ternary and quaternary stabilizer systems were almost similar in LDPE, iPP and EP matrices. The binary system of oligomeric HAS and tert-HAS has shown the antagonistic effect of stabilization, whereas their combination with organo-phosphite has exhibited synergistic effect even at higher doses of γ-sterilization. The combination of oligomeric HAS, tert-HAS, organo-phosphite and hindered phenol exhibited improved stabilization efficiency than single or binary additive systems. The phenol systems have shown long term of stability than that of phenol-free systems. It was found that the consumption of oligomeric stabilizer significantly depends on the components of stabilization mixture. It was concluded that the stability of polyolefins (LDPE, iPP and EP) against γ-sterilization can be achieved by blends of different stabilizers which are approved for food contact applications.